Amino acids at position 5 in the peptide/MHC binding region of a public virus‐specific TCR are completely inter‐changeable without loss of function. Issue 11 (19th October 2022) - Huisman, Wesley; de Gier, Melanie; Hageman, Lois; Shomuradova, Alina S.; Leboux, Didier A.T.; Amsen, Derk; Falkenburg, J.H. Frederik; Jedema, Inge
Abstract: Anti‐viral T‐cell responses are usually directed against a limited set of antigens, but often contain many T cells expressing different T‐cell receptors (TCRs). Identical TCRs found within virus‐specific T‐cell populations in different individuals are known as public TCRs, but also TCRs highly‐similar to these public TCRs, with only minor variations in amino acids on specific positions in the Complementary Determining Regions (CDRs), are frequently found. However, the degree of freedom at these positions was not clear. In this study, we used the HLA‐A*02:01‐restricted EBV‐LMP2 FLY ‐specific public TCR as model and modified the highly‐variable position 5 of the CDR3β sequence with all 20 amino acids. Our results demonstrate that amino acids at this particular position in the CDR3β region of this TCR are completely inter‐changeable, without loss of TCR function. We show that the inability to find certain variants in individuals is explained by their lower recombination probability rather than by steric hindrance. Abstract : In this study, the HLA‐A*02:01‐restricted EBV‐LMP2 FLY ‐specific public TCR was used as model and the highly‐variable position 5 of the CDR3β sequence was substituted with all 20 amino‐acids. Our results demonstrate that amino‐acids at this particular position in the CDR3β region of this TCR are completely inter‐changeable, without loss of TCR function